2008
DOI: 10.1038/ijir.2008.2
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for the existence of an estrogen-responsive sexually dimorphic group of cells in the medial preoptic area of the 129SvEv mouse strain

Abstract: The current study describes the presence of sexually dimorphic cell groups within the MPO of the 129SvEv, but not the C57BL/6J strain of mice. We detected galanin-positive clusters of cells located in the MPO of 129SvEv and C57BL/6J mice, with sex differences found only in the 129SvEv strain. Aromatase-positive and dense Nissl-counterstained clusters of cells were identified only in the MPO of 129SvEv mice, but not in the C57BL/6J strain. Furthermore, this study has demonstrated that the volume of these sexual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
1

Year Published

2010
2010
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 36 publications
0
5
1
Order By: Relevance
“…More than one article has described the lack of preoptic sexual dimorphism in one of the most widely used mouse strains, C57BL/6J (Hill et al, 2008), by Nissl staining or by using galanin or aromatase immunoreactivity (Brown et al, 1999;Hill et al, 2008). Unlike in other species, sexual dimorphic structures in the mice, when present, were in some cases larger in females than in males, as in the Nissl-stained anteroventral periventricular nucleus in the present study.…”
Section: Sexual Dimorphism In the Mouse Preoptic Areacontrasting
confidence: 56%
See 1 more Smart Citation
“…More than one article has described the lack of preoptic sexual dimorphism in one of the most widely used mouse strains, C57BL/6J (Hill et al, 2008), by Nissl staining or by using galanin or aromatase immunoreactivity (Brown et al, 1999;Hill et al, 2008). Unlike in other species, sexual dimorphic structures in the mice, when present, were in some cases larger in females than in males, as in the Nissl-stained anteroventral periventricular nucleus in the present study.…”
Section: Sexual Dimorphism In the Mouse Preoptic Areacontrasting
confidence: 56%
“…The cluster of galanin-immunoreactive neurons in the 129SvEv mouse POA also does not depend on androgen. Aromatase gene knockout (KO) mice with the 129SvEv background, which have higher titers of testosterone, exhibit a feminine size of this structure (Hill et al, 2008). It may be that the reported cluster in the POA is different from the aggregate of CB neurons in the present study, because the galanin-immunoreactive cluster lacks a sex difference in C57BL/6J mice and cannot be visualized by Nissl staining (Hill et al, 2008).…”
Section: Lack Of Effect Of Dhtmentioning
confidence: 74%
“…Aromatase knockout (ArKO) female mice are infertile as their reproductive organs do not develop properly (Simpson, 2004). These mice show impaired functionality in the amygdala and hypothalamus (Pierman et al, 2008) and increased apoptosis in the frontal cortex (Hill et al, 2008). Various studies on ArKO mice have implicated estrogen in neurodevelopment (Balthazart et al, 1991;Sasahara et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Morale et al ( 42 ) suggested that the inhibition of cytochrome p450 aromatase function contributes to Parkinson's disease. Others have demonstrated that female mice are infertile when the aromatase gene is silenced, as their reproductive organs cannot develop properly ( 43 ), that the function of the amygdala and hypothalamus in these mice is impaired ( 44 ) and that apoptosis in the frontal cortex is increased ( 45 ). Numerous studies on aromatase knockout mice have suggested that estrogen is important for neurodevelopment ( 46 ).…”
Section: Discussionmentioning
confidence: 99%